Development Strategy Of Banana Island Marine Tourism (Study on the Tourism Office of West Pesisir Regency) - Yanuar Rikardo (Penerbit Jurnal Indonesia, 2023)
The research aims to describe the Pisang Island Marine Tourism Development Strategy (study at the West Pesisir Regency Tourism Office). The type of research used is descriptive-qualitative. The method for determining informants used purposive sampling of six people, consisting of 1 department head, 3 department heads, and 2 community members. The informants in this research were Head of the Tourism Service, Head of the Tourism and Culture Promotion Section, Head of Division, Visitors, and Community Figures on Pisang Island. The data analysis method used is descriptive-qualitative. Based on the results of research and discussion, it is known that the West Pesisir Regency Tourism Office, in developing Pisang Island marine tourism, has carried out an annual programme regarding the development of Pisang Island marine tourism as it should be. This can be seen from several data indicators of effective work achievement. However, there is one obstacle that occurs in the implementation of the programme for increasing infrastructure and tourist attraction development due to the lack of budget absorption for tourism attraction development activities in Pesisir Barat Regency, plus the budget is not optimal because the proposed budget revision to the centre is not submitted quickly enough, and there is a lack of connection between the regional and central vernments. In fact, the Regional Regulation concerning RIPPDA No. 07 of 2017 has been well implemented by the West Pesisir Regency Tourism Office. It is necessary to suggest that the West Pesisir Regency government, especially the West Pesisir Regency Tourism Office, must have a creative spirit so that the development of Banana Island tourism continues.